EVALUATING THE IMPACT OF COMMUNITY-BASED REHABILITATION MODELS ON FALL PREVENTION AND QUALITY OF LIFE IN THE ELDERLY (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aims to evaluate the effectiveness of community-based rehabilitation models in reducing the risk of falls and improving quality of life indicators in the elderly.Subjects and methods: A community-based intervention study, a pre- and post-intervention comparative design, was conducted on 120 individuals aged 60 and over at risk of falls. The 6-month intervention program included balance training, muscle strengthening, and safety education. Fall risk was assessed using the Berg balance scale and the TUG. Quality of life was measured using the EQ-5D-5L scale at the time points before and after the intervention.Results: After 6 months, the percentage of elderly individuals reporting falls decreased significantly from 42.6% to 15.3% (p < 0.001). The average Berg balance score increased significantly from 41.2 ± 4.5 to 48.6 ± 3.2 points (p < 0.05), indicating restored balance function. The time to complete the TUG test decreased from 14.5 ± 2.1 seconds to 11.2 ± 1.8 seconds (p < 0.01). Regarding quality of life, the EQ-5D index score increased from 0.62 ± 0.15 to 0.78 ± 0.12 (p < 0.05). Notably, 82.5% of subjects reported a reduction in fear of falling syndrome.Conclusions: Community-based rehabilitation models are highly effective, significantly reducing the risk of falls and comprehensively improving the quality of life for the elderly. This model needs to be replicated at the primary healthcare level.
Keywords: Community-based rehabilitation, falls, quality of life, elderly, TUG, Berg balance scale.